2013
DOI: 10.1016/j.ultsonch.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted oxidative desulfurization of bunker-C oil using tert-butyl hydroperoxide

Abstract: This work investigated the ultrasonic assisted oxidative desulfurization of bunker-C oil with TBHP/MoO3 system. The operational parameters for the desulfurization procedure such as ultrasonic irradiation time, ultrasonic wave amplitude, catalyst initial concentration and oxidation agent initial concentration were studied. The experimental results show that the present oxidation system was very efficient for the desulfurization of bunker-C oil and ~35% sulfur was removed which was dependent on operational param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Most studies used highly polar solvents like acetonitrile, N, N-dimethylformamide (DMF), methanol, butyrolactone, or N, N-dimethylpyrrolidone for extraction. While for the model feed containing initially DBT or 4,6-DMDBT acetonitrile and methanol has been demonstrated as a very efficient extraction solvent [28,[43][44][45], the nature of the feedstock influences the choice of solvent for high sulfur content and heavy feedstock. Acetonitrile was found suitable for the extraction due to its relatively low boiling point at 355 K compared to sulfones (550 to 950 K) which facilitates separation and reuse of solvent.…”
Section: Sulfones Separationmentioning
confidence: 99%
“…Most studies used highly polar solvents like acetonitrile, N, N-dimethylformamide (DMF), methanol, butyrolactone, or N, N-dimethylpyrrolidone for extraction. While for the model feed containing initially DBT or 4,6-DMDBT acetonitrile and methanol has been demonstrated as a very efficient extraction solvent [28,[43][44][45], the nature of the feedstock influences the choice of solvent for high sulfur content and heavy feedstock. Acetonitrile was found suitable for the extraction due to its relatively low boiling point at 355 K compared to sulfones (550 to 950 K) which facilitates separation and reuse of solvent.…”
Section: Sulfones Separationmentioning
confidence: 99%
“…H 2 O 2 , an oxidant widely used in supercritical gasification oxidative reactions, shows considerable efficiency in the oxidation/destruction of biomass . The second oxidant agent (t‐BHP) is typically used in syntheses reactions, epoxidation, and hydrodesulphurization oil, among others, and has not yet been reported in the literature as an oxidant in gasification reactions.…”
Section: Resultsmentioning
confidence: 99%
“…The author also found that higher desulfurization efficiency was obtained within a shorter reaction time as compared to the traditional mixing ODS process [61]. Some studies have also reported the successful result of ultrasound assisted oxidative desulfurization of fuel oil performed under mild reaction conditions [62][63][64][65][66][67]. One summary table for oxidative catalytic desulfurization of liquid fuel oil has been presented at the end (Table 1).…”
Section: Ultrasound-assisted Oxidation Systemmentioning
confidence: 96%